Surrounding Rock Movement of Steeply Dipping Coal Seam Using Backfill Mining. (12th May 2021) - Lv, Wenyu; Guo, Kai; Yu, Jianhao; Du, Xufeng; Feng, Kun
Abstract : The movement of the overlying strata in steeply dipping coal seams is complex, and the deformation of roof rock beam is obvious. In general, the backfill mining method can improve the stability of the surrounding rock effectively. In this study, the 645 working face of the tested mine is used as a prototype to establish the mechanical model of the inclined roof beam using the sloping flexible shield support backfilling method in a steeply dipping coal seam, and the deflection equation is derived to obtain the roof damage structure and the maximum deflection position of the roof beam. Finally, numerical simulation and physical similarity simulation experiments are carried out to study the stability of the surrounding rock structure under backfilling mining in steeply dipping coal seams. The results show the following: (1) With the support of the gangue filling body, the inclined roof beam has smaller roof subsidence, and the maximum deflection position moves to the upper part of working face. (2) With the increase of the stope height, the stress and displacement field of the surrounding rock using the backfilling method show an asymmetrical distribution, the movement, deformation, and failure increase slowly, and the increase of the strain is relatively stable. Compared with the caving method, the range and degree of the surrounding rock disturbed by the mining stress are lower. The results of numerical simulation and physical similarity simulation experiment are generally consistent with the theoretically derived results. Overall, this study can provide theoretical basis for the safe and efficient production of steeply dipping coal seams.